THE INFLUENCE OF INDONESIAN LANGUAGE ON STUDENTS’ SPEECH AT THE ENGLISH STUDY PROGRAM OF FKIP UNIVERSITAS RIAU - Jismulatif, Jismulatif; Delfi, Syofia; Nur’ajilah, Raja Shabrina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was a descriptive research of the influence of Indonesian Language on students’ speech at the English Study Program FKIP Universitas Riau. The aim of this research was to know whether or not the Indonesian Language influenced the students’ speech at the English Study Program of FKIP Universitas Riau. The population of this research was the fourth year (8th Semester) students of English Department (2013)of FKIP Universitas Riau with total 90 students. The sample of this research was 25% of the total population which was 23 students. The instrument of this research was interview. In conducting this research, there were five topics in interview which used to know the students’ speech based on three language components: syntactic, lexical, and phonological. To get the quantitative data in this research, one rater was involved to analyze the errors that the students made. From the result of the oral test, the writer concluded that the percentage of the influence on students’ speech in terms of syntactic was 26.08%. The percentage of influence on students’ speech in terms of lexical was 14.49%. The percentage of influence on students’ speech in terms of phonological was 28.98%. The students’ influence score was 69.56% which was categorized as positive. The research finding also shows that Indonesian Language influenced the students’ speech in terms of phonological the most. Therefore, the students should pay attention on learning and practice speaking English more. The educators could also help the students to listen to the correct pronunciation that the educator has modeled, so that they’ll be able to pronounce the words correctly.Keywords : speech, influence, Indonesian language